Effect of supplementation of depleted, non-milking, non-cycling F1 crossbred cows on time of repletion and resumption of reproductive activity - Zerbini, E.; Gebre-Wold, A.; Gemeda, T.; Demissie, D. (Ethiopian Society of Animal Production, 1995)
Twelve non-milking, non-cycling F1 crossbred dairy cows (Friesian x Boran and Simmental x Boran) in low body weight and body condition were stratified to 2 diets according to parity, body weight, body condition score and calving intervals to estimate time necessary to resume reproductive activity. The diets were: (1) H: natural grass hay fed ad libitum and mineral lick + 3 kg of concentrate, and (2) diet H + P: H + seven hours per day natural pasture grazing. Daily dry matter intake was similar between the two diets, but total intake of N was about 10 percent for cows with access to pasture. The calculated ME intake was more than twice the estimated maintenance requirement for both diets. Live weights and body condition scores were not significantly different between diets. There were large and visible changes in body condition when different reproductive events occurred and body condition score was greater for H + P than H cows at first estrus and at conception: At 45 days of repletion, cows were already ovulating with no significant differences between diets. On the other hand, days to onset of oestrus tended to be greater for cows fed the H than H + P diet (83 vs 44, respectively). Time to conception was not different between diets. Conception occurred when cows had recovered 0.51 and 0.58 of their live weight loss and 0.93 and 1.11 of their intitial body condition for cows in the H and H + P diets, respectively. The time to achieve repletion weight was 139 and 178 days for cows receiving H + P and H diets, respectively. Cows subjected to an exceptionally long depletion period were able to resume ovarian activity and to conceive in less than three months when fed twice maintenance requirements. These results have important implication for on-farm situations in Ethiopia where large fluctuations of feed availability occurs.